INFLUENCE OF MAIN, REPEATED, AND INTERMEDIATE CROPS ON INCREASING COTTON YIELD IN SHORT-ROTATION CROP SYSTEMS - Haydarovich, Mahmudov Utkir; Meylikovich, Khalikov Bahodir (Research Focus International Scientific Journal, 2026)
The article presents the results of long-term (2022-2025) experiments on the influence of main and repeated crops of crotalaria (crotalaria juncea), intermediate crops of safflower (trifolium alexandrinum) and bermuda grass (trifolium resupinatum), and winter wheat on increasing cotton yields in short-term crop rotations under the conditions of typical sierozem soils of the Tashkent region. The results showed that when sowing crotalaria for one year with subsequent sowing of the intermediate crop shabdar + bersim, when sowing cotton for the second year and sowing winter wheat for the first year with subsequent sowing of the repeated crop crotaly, when sowing the intermediate crop shabdar + bersim, when sowing cotton for the second year and sowing winter wheat for the first year with subsequent sowing of the repeated crotaly when sowing winter wheat for the second year with subsequent sowing of the repeated crotalaria with subsequent sowing of the intermediate crop shabdar + bersim, the yield was 49.0-48.3-49.4 c/ha compared to the long-term and control variants.